Diagenesis of clastic ores of the Ishkininо Co-bearing massive sulfide deposit (Southern Urals): Mineralogical-geochemical data and thermodynamic modeling - Melekestseva, I. Yu; Maslennikov, V. V.; Tret’yakov, G. A. (Litosfera (Ekaterinburg. Online), 2022)
Research subject. The transformed clastic ores (ore diagenites) of the Ishkinino Co-bearing massive sulfide deposit hosted by serpentinites of the Main Uralian Fault Zone. Materials and methods. The structures and textures of the ores were stu died. The trace element contents of sulfides and oxides were determined using LA ICP MS. The physical and chemical modeling of the diagenetic formation of accessory As minerals was conducted using the Selektor program package. Results. The clastic ores are transformed gravelites with angular and rounded clasts of serpentinites, sulfides and chromite in the psammitic matrix of the same mineral composition. No hydrothermal minerals remain in gravelites; they are replaced by crystalline pyrite-2, porous pyrite-3, anhedral pyrite-4, pyrrhotite, chalcopyrite and magnetite. Chalcopyrite and magnetite replace all sulfides, sulfarsenides, chromite and gangue minerals. Chromite occurs as fragmented crystals or inclusions into serpentinite clasts. The matrix hosts euhedral cobaltite crystals with nickeline, gersdorffite and native gold inclusions. Crystalline pyrite-2 is characterized by higher Mn, Co, Ni, Cu and Zn contents. Porous pyrite-3 exhibits higher Co, Cu and Se contents. Anhedral pyrite-4 is enriched in most trace element contents in comparison with other sulfides and pyrite generations. Chalcopyrite is characterized by higher contents of Zn and Se. Pyrrhotite contains the highest Ni and hi gher Co contents. Conclusions. The main trace elements in the ores of the deposit (Co and Ni), as well as Cu, Zn and Mn, are hosted not only in sulfides, but also in oxides. Thus, chromite contains Zn and Ni, while magnetite contains Mn and Cu. Selenium occurs in all sulfides in similar quantities. Tellurium is mostly concentrated in pyrite-4. A comparative analysis of our results with those reported on other massive sulfide deposits showed that the serpentinite-sulfide gravelites of the Ishkinino deposit had been intensely transformed during diagenesis, which resulted in low trace element contents in diagenetic sulfides. The diagenetic alteration of clastic ores led to the formation of authigenic cobaltite, gersdorffite, nickeline and native gold as a result of trace element release from primary hydrothermal minerals. Thermodynamic mode ling showed the possibility of formation of As-bearing minerals (in particular, nickeline) at temperatures of 200°C and below.